2018
DOI: 10.1007/s10902-018-9998-7
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Trait Gratitude and Psychological Wellbeing in University Students: The Mediating Role of Affective State and the Moderating Role of State Gratitude

Abstract: Gratitude is a positive psychological characteristic that is connected to wellbeing. This study aims to examine the relation between trait gratitude and psychological wellbeing (PWB), as well as the mediational role of the affective state in the relationship between these concepts. Moreover, we also investigated whether state gratitude moderates the relation between trait gratitude, affective state, and PWB. Participants were 135 undergraduate students who completed a battery of assessments as part of a standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 50 publications
(109 reference statements)
3
23
0
1
Order By: Relevance
“…Firstly, this study found that state gratitude inhibits situational envy, which proved H1. This result is basically consistent with previous studies; that is, gratitude is negatively correlated with negative emotions (Măirean, Turliuc, & Arghire, 2019; Watkins et al, 2003; Wood, Maltby, Gillett, et al, 2008). Meanwhile, there is also a significant negative correlation between gratitude and envy (McCullough et al, 2002, 2004; Solom et al, 2017), and gratitude can also affect envy (Xiang et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Firstly, this study found that state gratitude inhibits situational envy, which proved H1. This result is basically consistent with previous studies; that is, gratitude is negatively correlated with negative emotions (Măirean, Turliuc, & Arghire, 2019; Watkins et al, 2003; Wood, Maltby, Gillett, et al, 2008). Meanwhile, there is also a significant negative correlation between gratitude and envy (McCullough et al, 2002, 2004; Solom et al, 2017), and gratitude can also affect envy (Xiang et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, the results reveal that all four subscales of gratitude were positively associated with positive affect and inversely associated with negative affect, indicating that people who are more grateful, both to other people and to transcendental forces, experience a better affective experience. This result is consistent with previous studies in which gratitude was related to various dimensions of well-being, conducted throughout the COVID-19 pandemic (e.g., Burke et al, 2020 ; Jiang, 2020 ), in other historical times of adversity (e.g., Coffman, 1996 ; Peterson and Seligman, 2003 ), and also in normative historical times (e.g., Mairean et al, 2019 ). However, the four subscales of gratitude were not related to FC.…”
Section: Discussionsupporting
confidence: 91%
“…According to Loi and Ng (2021), fostering a grateful mindset could enhance well-being. Gratitude influences several positive changes in the emotional state, hence boosting the levels of psychological well-being of the person (Măirean, Turliuc, & Arghire, 2019). Gratitude also contributes to well-being by increasing the retrieval of positive memories or experiences of the individuals (Sheldon, Kashdan, & Steger, 2010).…”
Section: Resultsmentioning
confidence: 99%